2016
DOI: 10.1080/23335432.2016.1229135
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sagittal plane kinematics, foot morphology and vertical forces applied to three regions of the foot

Abstract: Kinetic analysis of human motion with a multi-segment musculoskeletal foot model requires the distribution of loading applied to the modeled foot segments to be determined. This work thus examines the existence of any correlation between intersegmental foot kinematics, foot morphology, and the distribution of vertical loading in a multi-segment foot model. Gait analysis trials were performed by 20 healthy subjects at a self-selected speed with intersegmental foot joint angles and the distribution of vertical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…All experiments used only one subject and one type of movement (gait), so the model developed in this paper should be considered a subject specific model. Using a single subject may limit the use of this model, but may be beneficial for accuracy, since subject-specific contact models tend to improve accuracy [30], [31], especially if intersegmental foot loading would be of interest due to the intersubject variability in foot morphology [32].…”
Section: Experimental Parametrisation Methodsmentioning
confidence: 99%
“…All experiments used only one subject and one type of movement (gait), so the model developed in this paper should be considered a subject specific model. Using a single subject may limit the use of this model, but may be beneficial for accuracy, since subject-specific contact models tend to improve accuracy [30], [31], especially if intersegmental foot loading would be of interest due to the intersubject variability in foot morphology [32].…”
Section: Experimental Parametrisation Methodsmentioning
confidence: 99%
“…The analysis of ground reaction force (GRF) (i.e., the force of interaction between the body, usually the foot, and the ground) is central in many scientific and engineering fields, including biomechanics, medical science, sports science, and robotics [ 1 , 2 , 3 , 4 ]. In human biomechanics and humanoid robotics, for example, postural control is critical for understanding balance and locomotion, where the control strategies for bipedal systems heavily rely on the knowledge of the GRF and its point of application, i.e., the centre of pressure (COP).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of foot morphology, shape, and posture Changes in tissue morphology, bone shape, and posture of the foot influence the biomechanics of the lower extremity. For example, foot types (mainly, normal, planus, and cavus feet) (Buldt et al, 2015a), foot posture (mainly, normal, pronated, and supinated feet) (Hollander et al, 2019), toe morphology (Mei et al, 2015a), hallux valgus (Hannah et al, 2016), and manipulated forefoot shapes (abducted hallux versus adducted hallux) (Mei et al, 2016;Xiang et al, 2020a;Xiang et al, 2020b) have been previously reported in the literature. Pathological conditions, such as diabetic-related foot deformities (Guiotto et al, 2013;Lu et al, 2015) can also influence the biomechanics.…”
Section: Foot Morphology Shape and Posture In Running Activitiesmentioning
confidence: 99%